Letting the World Run About: Poetry from all over - Perkins, Elizabeth (LiNQ (Literature in North Queensland), 2016)
Elizabeth Perkins reviews: Doris Brett, In the constellation of the crab, Hale & Iremonger, Sydney, 1996. 64 pp. ISBN 0 86806 603 6. John A. Scott, Selected Poems. UQP, St Lucia, 1995. 281 pp. ISBN 0 7022 2688 2. Barry O'Donohue, Portrait of a Survivor. Queensland Community Press, Brisbane, 1995. 119 pp. ISBN 0 949736 14 7. Philip Hammial, Just Desserts. Island Press Cooperative, Woodford, 1995. 71pp. ISBN 0 909771 56 1. Peter Skrzynecki. ed., The Breaking Line. Youngstreet Poets 5. Youngstreet Poets, Sydney, 1995. 92 pp. ISBN 0646 22914 1. Going Down Swinging 15. Clifton Hill, Victoria. 192 pp. ISSN 0157 3950. Phil Ilton, Capsules. Medal Poets Series 28. Denlynne Publications, Kuranda Q., 1996. 56 pp. ISBN 0 646 27537 2. Connie Barber, Enter Your House With Care. Medal Poets Series 29. Denlynne Publications, Kuranda Q., 1996. 80 pp. ISBN 0 646 27538 0. William Hart-Smith. Birds Beasts and Flowers. Australian Children's Poetry. ed. Brian Dibble. Puffin Books, Ringwood, 1996. 108 pp. ISBN 0 14 037724 7.